Characterization and Classification of Cold Wave Conditions in Rocky Terrains of Jaisalmer District in Thar Desert - Kandpal, B K; Mertia, R S (Annals of Arid Zone, 2016)
The study was conducted to find out the occurrence of low temperature phenomenon in rocky terrain of Jaisalmer predominated by typical run off farming system called Khadin. Daily minimum temperature data for 26 years (1981-2006) were used to estimate mean minimum weekly temperature (Tmin) and absolute mean minimum weekly temperature (TLeast) from standard meteorological weeks 45 to 10. Based on Tmin and TLeast values the weeks were grouped into average/maximum chilling (